Similarity in parasite community structure may be used to trace latitudinal migrations of Odontesthes smitti along Argentinean coasts - Carballo, María Cecilia (2011)
The aims of this study were to determine the existence of migratory movements and to identify ecological stocks of the silverside Odontesthes smitti along its distribution in the Southern Atlantic Ocean, using metazoan parasites as biological tags. Samples were obtained from San José Gulf (SJ) (42° 25′ S; 64° 07′ W) and Nuevo Gulf (NG) (42° 47′ S; 65° 02′ W) in north Patagonia during winter and summer and in waters of Mar del Plata (MDP) (38° 03′ S; 57° 32′ W), Bonaerense region, during winter. Fifteen parasite species were collected. Multivariate statistical procedures on parasite community data showed strong effect of host size on the structure of parasite assemblages. Taking into account the variations among samples due to host size, the differential structure of parasite communities between SJ and NG suggests that fish inhabiting these localities could belong to different ecological stocks. Fish from MDP and SJ caught in summer showed similar composition in their parasite assemblages, which is congruent with a migratory cycle that implies that fish caught in MDP during winter inhabit SJ during summer. Further evidence of the Patagonian origin of MDP O. smitti is the presence of the digenean Proctotrema bartolii in fish from both regions. Proctotrema bartolii is acquired by O. smitti only in the Magellanic province, where its intermediate host, Darina solenoides, is distributed. The analyses suggest that O. smitti inhabiting north Patagonian gulfs could belong to different ecological stocks and that O. smitti caught in MDP could have come from SJ.